2019
DOI: 10.1016/s2468-2667(19)30145-8
|View full text |Cite
|
Sign up to set email alerts
|

Life course health consequences and associated annual costs of adverse childhood experiences across Europe and North America: a systematic review and meta-analysis

Abstract: Background An increasing number of studies are identifying associations between adverse childhood experiences (ACEs) and ill health throughout the life course. We aimed to calculate the proportions of major risk factors for and causes of ill health that are attributable to one or multiple types of ACE and the associated financial costs. Methods In this systematic review and meta-analysis, we searched for studies in which risk data in individuals withACEs were compared with these data in those without ACEs. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
621
2
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 674 publications
(651 citation statements)
references
References 46 publications
19
621
2
9
Order By: Relevance
“…Persons reporting more types of adverse childhood experiences were at highest risk. These findings are consistent with those from similar analyses conducted in England, Europe, and North America ( 1 , 2 ) and suggest that preventing adverse childhood experiences might reduce occurrences of the outcomes examined, with potential reductions ranging from 1.7% (overweight or obesity) to 44.1% (depression). Given these findings, preventing adverse childhood experiences could have broad positive health, social, and economic impacts.…”
Section: Discussionsupporting
confidence: 88%
“…Persons reporting more types of adverse childhood experiences were at highest risk. These findings are consistent with those from similar analyses conducted in England, Europe, and North America ( 1 , 2 ) and suggest that preventing adverse childhood experiences might reduce occurrences of the outcomes examined, with potential reductions ranging from 1.7% (overweight or obesity) to 44.1% (depression). Given these findings, preventing adverse childhood experiences could have broad positive health, social, and economic impacts.…”
Section: Discussionsupporting
confidence: 88%
“…Prior reviews have revealed the long-term effects of ACEs on developmental disruptions, negative adult psychological and physical health outcomes, risky health behaviors, increased healthcare utilization [ 5 , 8 12 ], and associated high societal financial burden [ 13 , 14 ]. The total annual costs attributable to ACEs for six causes of ill health (cancer, diabetes, cardiovascular disease, respiratory disease, anxiety, depression) is estimated to range between US$417 and $487 billion in Europe and North America, with over 75% of the cost arising in individuals with two or more ACEs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Awareness on consent, from early ages, has to do with freedom, shaping the limits of one's own body and that of the other person. Duress, coercion and any similar kinds of acts committed by another individual, are considered harmful and they can potentially involve seriously adverse life-course health consequences (Bellis et al, 2019). Indeed, sexual harassment and gender-based violence have serious negative repercussions on people's physical and mental health (World Health Organization [WHO], 2018).…”
Section: Introductionmentioning
confidence: 99%